A new subspecies of the Australian Ringneck (Barnardius zonarius) from the Upper Cooper Creek Drainage, Lake Eyre Basin, central Australia. (1st December 2016) - Forshaw, Joseph M.; Joseph, Leo
Abstract: A new, apparently isolated subspecies of the Australian Ringneck Parrot ( Barnardius zonarius ) is described from the Upper Cooper Creek drainage in far north-eastern South Australia and neighbouring extreme south-western Queensland. If two species are recognised in Barnardius, this form would be a subspecies of B. barnardi. http://zoobank.org/urn:lsid:zoobank.org:pub:A2083683-6FAE-4D3F-9B2A-BAA0C47AC8FF